1999
DOI: 10.1161/01.str.30.12.2651
|View full text |Cite
|
Sign up to set email alerts
|

Primary Somatosensory Cortex Activation Is Not Altered in Patients With Ventroposterior Thalamic Lesions

Abstract: Background and Purpose-We know remarkably little about the mechanisms underlying cortical activation. Such mechanisms might be better understood by studying the effect of well-localized lesions on the cortical activations in simple paradigms. Methods-We used H 2 15 O and positron emission tomography to measure regional cerebral blood flow (rCBF) at rest and during hand vibration in 7 patients with unilateral thalamic lesion involving the ventroposterior (VP) somatosensory thalamic relay nuclei. We compared the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…There are 2 main findings: (1) Lesions involving the ventroposterior group of thalamic relay nuclei did not eliminate cortical activations associated with tactile stimulation of the strokeaffected hand, similar to the results of Remy et al 10 ; and (2) despite this unaffected primary representation, ipsilesional SI activation was abolished in all 4 patients with bilateral tactile stimulation early after stroke. Reversal of this attenuation was associated with recovery over time.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…There are 2 main findings: (1) Lesions involving the ventroposterior group of thalamic relay nuclei did not eliminate cortical activations associated with tactile stimulation of the strokeaffected hand, similar to the results of Remy et al 10 ; and (2) despite this unaffected primary representation, ipsilesional SI activation was abolished in all 4 patients with bilateral tactile stimulation early after stroke. Reversal of this attenuation was associated with recovery over time.…”
Section: Discussionsupporting
confidence: 74%
“…In particular, in a series of 7 thalamic stroke patients, Remy et al 10 reported a reduction in resting regional blood flow in SI but not in response to hand vibration associated with lesions in the ventroposterior nuclei. The patients reported here (except perhaps patient 4) all had small lesions affecting the ventroposterior nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Sii, located in the parietal operculum adjacent to the dorsal insula, has been shown to connect directly with the thalamus through thalamocortical pathways without a relay in Si [47][48][49][50][51][52][53] . in addition, bilateral receptive fields of Sii respond to both contra-and ipsilateral stimuli [35,53] and to callosal connections from the Sii area of the opposite hemisphere [54] .…”
Section: Contribution Of the Secondary Somatosensory Cortexmentioning
confidence: 99%
“…Unlike many other studies on the role of sensory nuclei of the thalamus in sensation, we did not use simple sensory stimuli like median nerve or finger electrical stimulation [5,6,[8][9][10][11], but relied on more cognitive tasks to test the patients' performance under thalamic stimulation. Moreover, the stimuli were designed so that the subjects could not use a three-dimensional shape and could not use stereognosis, but had to rely mostly on fine touch.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the role of the human thalamus in sensation have focused on very simple tests like median or tibial nerve electrical stimulation or finger vibration [5][6][7][8][9][10][11][12][13]. Yet, in another set of experiments, general behavioral and psychological performance of patients in whom the thalamus is somehow involved was investigated [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%